Metastasis of Basal Cell Carcinoma to The Right Ventricle - Torlak, Zuhal; Uğurlucan, Murat; Göktaş, Burçe; Uçar, Adem; Sayın, Ömer Ali; Göksel, Onur; Dayıoğlu, Enver (Fırat University, 2012)
Metastatic tumors of the heart are more frequent when compared with the primary tumors. Among them the most common are the carcinomas. Autopsy series demonstrate secondary cardiac tumors to be 20 to 40 times more frequent than the primary masses. When a patient with a known carcinoma, being either treated or not treated, presents with the symptoms of heart failure and cardiyomegaly during the course of the disease, cardiac metastasis of the tumour should be considered in the first order. In this article, we present a patient who presented with the symptoms of heart failure and found to have most probably metastasis to the right ventricle by transthoracic echocardiography. The patient had undergone surgical treatment in 2006 for bazal cell carsinoma that developed on marjolin ulcer basis on the right leg.

Kalpte, metastatik tümörler primer tümörlere göre oldukça sık görülmektedir. Bunların çoğunu karsinomlar oluşturur. Otopsi raporları göstermektedir ki, kalbin sekonder tümörleri primer tümörlerine oranla 20-40 kat daha sık karşımıza çıkmaktadır. Herhangi bir tedavi görmüş olsun yada olmasın bilinen karsinoması olan bir olgunun klinik seyrinde kardiyomegali ve kalp yetmezliği semptomlarının ortaya çıkması durumu kardiyak metastazı akla getirmelidir. Bu makalede, sağ alt ekstremitede, Marjolin ülser zemininde gelişen bazal hücreli karsinom nedeni ile 2006 yılında opere olan hastada operasyondan 6 ay sonra kalp yetmezliği gelişmesi üzerine, yapılan transtorasik ekokardiografide sağ ventrikülde ön planda metastaz düşündüren kitle bulgusu olan hasta tartışılmıştır.
Bazal Hücreli Karsinomun Sağ Ventriküle Metastazı